2019
DOI: 10.1096/fj.201901662r
|View full text |Cite
|
Sign up to set email alerts
|

A centrosome‐localized calcium signal is essential for mammalian cell mitosis

Abstract: Mitosis defects can lead to premature ageing and cancer. Understanding mitosis regulation therefore has important implications for human disease. Early data suggested that calcium (Ca2+) signals could influence mitosis, but these have hitherto not been observed in mammalian cells. Here, we reveal a prolonged yet spatially restricted Ca2+ signal at the centrosomes of actively dividing cells. Local buffering of the centrosomal Ca2+ signals, by flash photolysis of the caged Ca2+ chelator diazo-2-acetoxymethyl est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The defects are reversed by expression of IP 3 R3, but only if it has a functional Ca 2+ pore ( Figure 4 ). This is consistent with recent work suggesting that local Ca 2+ signals occur near centrosomes throughout mitosis, and abolishing them at one centrosome perturbs mitosis ( Helassa et al., 2019 ). It is noteworthy that variations in expression of endogenous IP 3 Rs are associated with the reliability of spindle alignment: WT cells with fewer IP 3 Rs are more likely to have misaligned spindles ( Figure S3 A).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The defects are reversed by expression of IP 3 R3, but only if it has a functional Ca 2+ pore ( Figure 4 ). This is consistent with recent work suggesting that local Ca 2+ signals occur near centrosomes throughout mitosis, and abolishing them at one centrosome perturbs mitosis ( Helassa et al., 2019 ). It is noteworthy that variations in expression of endogenous IP 3 Rs are associated with the reliability of spindle alignment: WT cells with fewer IP 3 Rs are more likely to have misaligned spindles ( Figure S3 A).…”
Section: Discussionsupporting
confidence: 93%
“…We conclude that Ca 2+ release through IP 3 Rs is required for the mitotic spindle to align appropriately, probably through regulation of astral microtubules by IP 3 R-evoked Ca 2+ signals ( Figure 4 D). Future experiments should assess whether the Ca 2+ signals that occur during metaphase ( Helassa et al., 2019 ) regulate microtubules and their motors or deliver Ca 2+ locally to the mitochondria to allow local delivery of ATP ( Zhao et al., 2019 ) and thereby regulation of microtubule activity. Our results reveal that IP 3 R-evoked Ca 2+ signals are an important means of regulating the mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies demonstrated that chromosome condensation is influenced by Ca 2+ [64] . In addition, spatial restriction of a genetically encoded Ca 2+ sensor detected a focally restricted centrosome-based Ca 2+ signal in mitotic cells [65] . These findings are helping to clarify the crucial yet incompletely defined link between Ca 2+ signaling, cell cycle progression, arrest and apoptosis [66] .…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion of Ca 2+ in the nucleus promotes transition of chromatin structure from fibrous to globular, chromosome condensation, mitosis and cell proliferation. [64] , [65] , [66] …”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal clustering at the intercellular bridge has been suggested to promote the activities at the cleavage furrow (Rajamanoharan et al, 2015). Recent data indicate that phosphoinositol-4-kinase-dependent lysosome exocytosis provides membranous material to the furrow, and inhibiting this process causes mitotic failures (Helassa et al, 2019). Before the final cut, the portioning of endolysosomal vesicles into daughter cells occurs in an ordered, yet imprecise, manner.…”
Section: The Separation and The Final Cut: Vesicles On The Movementioning
confidence: 99%